The Implementation of Paris Agreement in Indonesia and the Impacts on Human Rights - Farhat Habibi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
The Paris Agreement serves as a global mechanism to address climate change. Indonesia, as one of the signatory countries, has implemented various policies and programs to fulfill its commitments. However, these actions have had significant impacts on human rights, particularly for low-income communities. This research aims to examine the implementation of the Paris Agreement at the national level and to assess the extent to which these actions have affected human rights. Using a normative legal approach and a qualitative method, government policies in combating climate change and their impacts on individuals’ rights have been analyzed. The theoretical framework of the research is based on environmental governance theory and human rights theory. The findings show that although Indonesia’s climate policies—including the establishment of relevant institutions and agencies, the integration of the Paris Agreement into national laws, changes in energy use, forest protection, and similar measures—have been effective in addressing climate change and reducing greenhouse gas emissions, they have, in many cases, resulted in human rights violations, especially concerning economic rights, the right to housing, and the right to health. These violations highlight the challenges in balancing environmental objectives with human rights protection and emphasize the necessity of integrating human rights considerations into climate change policies, along with providing compensatory measures when these rights are adversely affected.